(3x+2y)(6x-4y)=0

Simple and best practice solution for (3x+2y)(6x-4y)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x+2y)(6x-4y)=0 equation:


Simplifying
(3x + 2y)(6x + -4y) = 0

Multiply (3x + 2y) * (6x + -4y)
(3x * (6x + -4y) + 2y * (6x + -4y)) = 0
((6x * 3x + -4y * 3x) + 2y * (6x + -4y)) = 0

Reorder the terms:
((-12xy + 18x2) + 2y * (6x + -4y)) = 0
((-12xy + 18x2) + 2y * (6x + -4y)) = 0
(-12xy + 18x2 + (6x * 2y + -4y * 2y)) = 0
(-12xy + 18x2 + (12xy + -8y2)) = 0

Reorder the terms:
(-12xy + 12xy + 18x2 + -8y2) = 0

Combine like terms: -12xy + 12xy = 0
(0 + 18x2 + -8y2) = 0
(18x2 + -8y2) = 0

Solving
18x2 + -8y2 = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '8y2' to each side of the equation.
18x2 + -8y2 + 8y2 = 0 + 8y2

Combine like terms: -8y2 + 8y2 = 0
18x2 + 0 = 0 + 8y2
18x2 = 0 + 8y2
Remove the zero:
18x2 = 8y2

Divide each side by '18'.
x2 = 0.4444444444y2

Simplifying
x2 = 0.4444444444y2

Take the square root of each side:
x = {-0.666666667y, 0.666666667y}

See similar equations:

| X-59=6(2x+3)-11 | | (2m^2+4m+5)(5m-4)= | | -3+n=37 | | d*3.141/0.136=18 | | -4(0.1x+0.5)-0.9=-0.5 | | -2(x+3)+11=11-3x | | d*3.141/.1036=18 | | 8+n=41 | | 5(-8n+1)=85 | | 8(x+1)+10x=9 | | (2x-9)(5x+4)= | | 7=15-Y | | X+44=3x-42 | | (d*3.141)/.1036=18 | | 2(y+6)=102 | | 4+p=-23 | | 7f-s=9 | | X+44=3x-44 | | x^2+2x-28=y | | 5(x+9)-5=72-3x | | 200+(.75*0)= | | 10d+7=37 | | d*3.141=18 | | d*pi=18 | | sp+13=33 | | 2e+20=40 | | 4f+6=2 | | 4x^2-21x+36=2x+8 | | 3x+10-5x=19-13x+11x-9 | | -2x+5=6x+9 | | 8x-5=9+3(x+7) | | (x*3.141)/.1036=18 |

Equations solver categories